A rare case of indirect inguinal hernia with ovary as content at a hospital of Visakhapatnam - Nudurupati, Ravi Kiran; P, Sudha Malini; Nallamalapu, Navya Reddy (Indian Journal of Case Reports, 2018)
A hernia is the protrusion of the small intestines or omentum or other organs through a defect in the abdominal wall. Inguinal herniain females is very rare and occurs in